2011
DOI: 10.1007/s00259-011-1846-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging with 68Ga-SSTR PET/CT and correlation to immunohistochemistry of somatostatin receptors in neuroendocrine tumours

Abstract: The highly significant correlation between SSTR2A and SSTR5 and the SUV(max) on the (68)Ga-DOTA-NOC PET/CT scans is concordant with the affinity profile of (68)Ga-DOTA-NOC to the SSTR subtypes and demonstrates the excellent qualification of somatostatin analogues in the diagnostics of NET. This study correlating somatostatin receptor imaging using (68)Ga-DOTA-NOC PET/CT with immunohistochemically analysed SSTR also underlines the approval of therapy using somatostatin analogues, follow-up imaging as well as ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 24 publications
6
82
1
3
Order By: Relevance
“…Indeed, 76.5% of MCCs of our series expressed at least one SSTR, which is in line with the proportion of tumours accurately detected by SRI [19,20,21]. Results from SRI are related to the SSTR expression on the immunohistochemistry of well-differentiated extracutaneous NETs [14,55,56,57]. In our cohort, patients had not been evaluated with SRI, so we could not evaluate the relationship between SSTR expression and SRI results.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, 76.5% of MCCs of our series expressed at least one SSTR, which is in line with the proportion of tumours accurately detected by SRI [19,20,21]. Results from SRI are related to the SSTR expression on the immunohistochemistry of well-differentiated extracutaneous NETs [14,55,56,57]. In our cohort, patients had not been evaluated with SRI, so we could not evaluate the relationship between SSTR expression and SRI results.…”
Section: Discussionsupporting
confidence: 57%
“…Also the high prevalence of sst 3 in pheochromocytoma and neuroendocrine tumors found in our investigations with UMB-5 corresponds well to earlier data obtained with polyclonal antibodies [4,21,27,41]. In contrast to these previous investigations showing primarily cytoplasmic immunoreactivity, the present study revealed a predominance of plasma membrane staining.…”
Section: Discussioncontrasting
confidence: 56%
“…Two papers reported how the 68 Ga-DOTANOC SUV max correlates with somatostatin receptor expression (9,23), and two investigated the potential prognostic role of SUV max in patients with neuroendocrine tumors with different primary sites (9,10). However, pNETs generally show more aggressive clinical behavior than other forms of NET (8,11), with 5-y survival rates ranging between 25% and 75% (2,24,25).…”
Section: Discussionmentioning
confidence: 99%